The effect of debt covenant and tunneling incentive on tax avoidance: The moderating role of firm size in mining companies - Damastu Tigo Prakoso; Diana Sari (WIM Solusi Prima, 2026)
This study aims to examine the effect of debt covenant and tunneling incentive on tax avoidance, with firm size serving as a moderating variable, in mining sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Tax avoidance is measured using the Effective Tax Rate (ETR), while debt covenant is proxied by the ratio of EBITDA to interest expense, tunneling incentive by controlling ownership, and firm size by the natural logarithm of total assets. This study employs a quantitative approach using purposive sampling, resulting in a sample of 28 companies with 140 firm-year observations. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA). The results indicate that debt covenant has a significant effect on tax avoidance as proxied by ETR, whereas tunneling incentive does not have a significant effect. In addition, firm size is unable to moderate the effects of either debt covenant or tunneling incentive on tax avoidance. The findings further suggest that greater debt covenant pressure is associated with higher ETR values, indicating lower levels of tax avoidance, while controlling ownership does not directly influence corporate tax behavior. This study contributes to the accounting and taxation literature and provides insights for regulators in monitoring corporate tax practices.